PENGARUH PEMBERIAN AIR PERASAN BUAH MENGKUDU (Morinda citrifolia) TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Sari, Indah Komala; Arisandi, Monalisa; Morika, Honesty Diana; Novrika, Bri (SCIENTIA JOURNAL, 2018)
Hypertension is an abnormal increase in blood pressure in arterial blood vessels continuously for more than one period. This occurs when the arterioles are constricting. Arteriole constriction makes blood difficult to flow and increases pressure against arterial walls. The prevalence of hypertension in West Sumatra province reaches 21.4%. Data from the Provincial Health Office of West Sumatra in 2017 hypertension is the 10 most common diseases suffered by the community with 69,500 people suffering from hypertension. Pharmacological therapies available for hypertension have not shown improvement in reducing blood pressure in hypertensive patients. Very necessary companion therapy that is non-pharmacological treatment is expected to be able to complete pharmacological treatment in reducing blood pressure by using noni juice juice (Morinda Citrifolia).This study used the design of Quasy Experiment with the approach of group pretest posttest design. This research was carried out in the Belimbing Health Center Working Area The number of samples in this study were 10 respondents with purposive sampling technique. Data analysis in this study using univariate and bivariate using dependent t-test. The results obtained, the average systolic blood pressure of 12 mmHg with a value (p Value 0,000) and diastolic 5 mmHg (p Value 0.015) means that there is an influence on the average blood pressure before and after being given Noni juice.Based on the results of the research that has been obtained, it is expected that health workers through the head of the Puskesmas can apply or use Noni fruit juice as an alternative treatment for hypertension.